OPERATOR EFFORT ON THE OPERATION OF THE KNAPSACK SPRAYER PUMPING LEVER - Lambrecht,Edson (2018)
ABSTRACT Several equipments are used in the application of agrochemicals by small scale farmers, with emphasis on the knapsack hand sprayer due to the low cost of acquisition and viability of use in different operating conditions. Although it is an equipment widely used, few studies have been developed in order to ascertain its functional characteristics. This study has the objective of presenting a methodology to measure the effort to which the operator is subjected in the activation of the pumping lever of knapsack hand sprayer verifying if these machines fit within the limitations foreseen by the Brazilian laws and international regulations. The methodology used was adequate to measure the operator's required efforts for the activation of knapsack hand sprayer. All sprayers tested with water have achieved satisfactory results by national standards, but only two by international regulations.